Internet Of Things Based Milling Machine Design Using Esp8266 Nodemcu - Hari Sabana; Akim M. H. Pardede; Marto Sihombing (PT. INOVASI TEKNOLOGI KOMPUTER, 2023)
This study presents the design and development of a grinding machine based on the Internet of Things (IoT) utilizing NodeMCU ESP8266. The primary objective of this project is to integrate IoT technology into the grinding machine to enhance control, monitoring, and grinding process efficiency. By using NodeMCU ESP8266 as the microcontroller connected to a WiFi network, the grinding machine can be accessed and remotely controlled through devices connected to the internet. Users can access this platform to monitor the machine's condition and control it as needed. In this research, the focus is on circuit design, software development, and overall system integration. The testing results are performed by sending commands to start the DC motor, monitoring the DC motor's speed value, monitoring the grinding status, lid closure button, and reset button. The testing results indicate that this IoT-based grinding machine provides better control, real-time monitoring, and efficiency in the grinding process. Thus, this research portrays a successful implementation of IoT in the machinery industry, opening opportunities for further development in this field